Employee Commitment toward Organization and their Career during the Merger of Bishwa Bikas Bank and Fewa Finance - Adhikari, Nabin Bahadur (Janapriya Journal of Interdisciplinary Studies, 2017)
Change is indispensible for the survival of the firm. Managing change become more challenging when it includes massive human involvement. This research paper aims to investigate employee commitment towards organization and own career during the merger. For this hypothesis were set to test under some constraints. The study applied empirical approach in which a survey questionnaire was used to collect quantitative data and other statistical techniques like Chi square test, Pearson correlation was applied and conclude that there is no effect of age factor in the determination of employee commitment towards the organization. Moreover the employee commitment towards their career has relative influence to employee commitment towards organization. Janapriya Journal of Interdisciplinary Studies, Vol. 5 (December 2016), page: 44-55